Analisis Perbandingan Efisiensi Bank Umum Syariah (BUS) dan Unit Usaha Syariah (UUS) dengan Metode Stochastic Frontier Analysis (SFA) Periode 2010-2014 - Hesti Kustanti; Astiwi Indriani (JURNAL STUDI MANAJEMEN ORGANISASI, 2016)
Efficiency is a parameter to measure the performance of a company or banking. This studywas conducted to analyze the efficiency of Islamic banking in Indonesia is made up ofSharia Commercial Banks (BUS) and Sharia Business Unit (UUS) using SFA (StochasticFrontier Analysis).The population of this research are 12 Sharia Commercial Banks and 22 Sharia BusinessUnit. Of the population, elected 10 Islamic Banks and 5 Sharia Business Unit withpurposive sampling. Input variables used in this study is the operational cost, total assetsand labor costs. While the output variable used is total financing. This study usesStochastic Frontier Analysis (SFA) with the production function and the intermediationapproach. SFA measurement results in the form of a score of 0-1, when getting close to 1,the more efficient the bank anyway. Independent sample t-test was used in this study tomeasure differences in the level of efficiency of each bank group.The results showed that in 2010-2014, Islamic banking has increased the efficiency of eachperiod. The average value of efficiency there is a 0.43994 Sharia Commercial Banks andSharia Business Unit amounted to 0.47654, so that it can be concluded that the UUSsuperior BUS. The results of hypothesis testing panel, that the total assets of a significantand positive effect on total financing, operating costs are not significant and positive effecton total financing, and labor costs are not significant and negative effect on totalfinancing. The test results on the independent sample t-test showed that there is nosignificant difference between the level of efficiency BUS and UUS.